Engineering of micro-barcodes and nano-barcodes. - Nur Shahzreen Mohd Taufik. (2012)
Barcode technology has provided much utility in its functions of tagging and tracking. With the advent of QR codes and the smartphone, barcode technology’s potential in other areas such as advertising, is only just being appreciated. Micro- and nano-barcodes are at the forefront of barcode research, but current results are yielded with the aid of multitudinous methods and super-specialized equipment. With the aim of proving both the possibility and viability of micro- and nano-barcode technology, this project presents improved results in micro- and nano-barcode fabrication, yielded with the standard laboratory processes of photolithography and pulsed potential electrodeposition. This paper concludes with some suggestions on the direction future research on microfabrication for barcode technology can take.